THEORETICAL FOUNDATIONS OF MOVEMENT GAMES (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article discusses the theoretical foundations of teaching children active games. The practice of educating the younger generation in our country testifies to the fact that games are one of the most important means of forming high moral and physical qualities in children and adolescents. It plays a particularly important role in the physical education of preschool and school-aged children, as it contributes to the preservation and strengthening of health, the normalization of physical development, and the comprehensive improvement of motor skills.